PENGARUH LITERASI KEUANGAN DAN GAYA HIDUP TERHADAP PERILAKU KEUANGAN PADA GENERASI MILENIAL DI KOTA BIMA - Husniah, Dinah; S, Ema; Aflyani, Aflyani; Juriatun, Juriatun (Jurnal PenKoMi : Kajian Pendidikan dan Ekonomi, 2024)
The millennial generation is a generation whose birth date ranges from 1982 to 2002 (Strauss & Howe, 1991). The millennial generation tends to use their money for consumptive activities. If this is not controlled properly it will have an impact on financial management activities. Financial planning is an important thing to learn, especially for young people (millennial generation) because good financial behavior can improve living standards, reduce the risk of financial disaster, invest optimally and accumulate wealth within a certain period of time. This research aims to prove the influence of financial literacy and lifestyle on financial behavior in the millennial generation in Bima City. This research uses a quantitative approach using a purposive sampling method for sampling. The data analysis method uses SPSS software. The research results show that financial literacy has a positive effect on financial behavior, while lifestyle has a negative effect on financial behavior.